Perspectives on History of Science: The Scientific Revolution and its Relationship with Christianity - Karat Gouvea da Silva, Luiz Cambraia [UNESP] (Univ Federal Rio Grande Sul, Programa Pos-graduacao & Historia, 2017)
This article aims to analyze the relationship between Christianity and the Scientific Revolution of the sixteenth and seventeenth centuries from the perspective of three thinkers who discuss the theme: Robert K. Merton, Klaas Woortmann, and Edward Grant. Contemporary academic debates have defended the hypothesis that religious thought had fundamental importance on the formation of the concept of modern science. These three authors, coming from different areas - Sociology, Anthropology, and History, respectively - show the complexity and the heterogeneity of the debate, each in its own way.
Keywords: Science; Christianity; Renaissance